2014
DOI: 10.4172/2165-7556.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motion Sickness on Encoding and Retrieval Performance and on Psychophysiological Responses

Abstract: Background: Motion sickness has previously been found to deteriorate performance. In complex working environments, sustained ability to perform despite motion sickness is crucial. This study focuses on effects of motion sickness on encoding and retrieval of words. In addition, the temporal development of psychophysiological responses and their relationship with perceived motion sickness were investigated. Methods:Forty healthy participants (20 male and 20 female, age 19-51) performed an encoding and retrieval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous studies have found a relationship between cognitive load and cybersickness (Bos, 2015; Jones, Le, et al, 2019; Sepich et al, 2022), but there is a lack of passenger vehicles studies on this matter. The proposed hypothesis is also aligned with the multiple resource theory, which states that mental operation performance degrades when the available attention resources are insufficient (Matsangas et al, 2014; Sjörs Dahlman et al, 2014). Inconsistencies across studies warrants further studies to understand the impact of task workload on MS. An alternative hypothesis for the model’s underestimation of MS is that the assumption of zero visual inertial input during task performance doesn’t effectively capture the passenger’s gaze movement.…”
Section: Resultsmentioning
confidence: 79%
“…Previous studies have found a relationship between cognitive load and cybersickness (Bos, 2015; Jones, Le, et al, 2019; Sepich et al, 2022), but there is a lack of passenger vehicles studies on this matter. The proposed hypothesis is also aligned with the multiple resource theory, which states that mental operation performance degrades when the available attention resources are insufficient (Matsangas et al, 2014; Sjörs Dahlman et al, 2014). Inconsistencies across studies warrants further studies to understand the impact of task workload on MS. An alternative hypothesis for the model’s underestimation of MS is that the assumption of zero visual inertial input during task performance doesn’t effectively capture the passenger’s gaze movement.…”
Section: Resultsmentioning
confidence: 79%
“…HR and HRV show almost no correlation to the SMSL in our setting. Many studies indicated that the HR increases, whereas the HRV decreases, with rising MS [3], [50], [54], [55], while other studies report no effects related to MS [49]. Preliminary results of the authors, presented in the supplementary material, indicate increased HRV for susceptible subjects compared to not susceptible ones.…”
Section: Discussionmentioning
confidence: 93%
“…One of the explanations could come from the experimental setup of this study compared to other studies that also induced motion sickness in the participants. Most past motion sicknessinducing studies involved the participants keeping their heads still and looking straight inside a rotating drum (or optokinetic drum) [46]. Alternatively, in some other studies, the participants must endure a virtual ride, such as a rollercoaster [45].…”
Section: Discussionmentioning
confidence: 99%